EFL Teachers’ Assessment Model of Higher Order Thinking Skills - Sahir, Sutriani; Arqam; Zulfah Fakhruddin; Ambo Dalle; Magdahalena Tjalla (Universitas Muhammadiyah Palu, 2024)
This result discussed about Higher Order Thinking Skills (HOTS) referred to a critical thinking process and creative thinking ability. The problem was teacher still can’t develop assessment relevant to the principle of HOTS aspect. The research was conducted to describe about the EFL teachers’ model assessment in assessing students’ Higher Order Thinking Skills, to describe the EFL teachers’ model assessment in assessing students’ higher order thinking relevant to the principle of the Higher Order Thinking Skills Evaluation. The research method was quantitative. The subject of the research is 3 english teacher. Data collected through teacher evaluation test, and to validity of the result was English rubric. The data analysis by define the research question, define the content to be included and define the units of analysis. The result of this research were as follow: 1) Assessment model develop by EFL teachers’ to assess students’ Higher Order Thinking Skills showed in various assessment with multiple choice while another assessment model was online multiple choice by integrating test in online text and another model were essay and fill the blank which regarding to the Higher Order Thinking evaluation test. 2) The Relevance of assessment and the principle of Higher Order Thinking showed first assessment scored 62% which categorized as not relevance. Second assessment scored 53% which categorized as relevance, third assessment showed scored 100% which categorized as relevance.